2024
DOI: 10.1108/pm-07-2023-0060
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the barriers facing corporate social responsibility in the built environment: Ghana’s perspective from a qualitative approach

Clinton Aigbavboa,
Andrew Ebekozien,
Emmanuel Kofi Afetorgbor
et al.

Abstract: Purpose Several organisations dedicate a portion of their budget and business websites to corporate social responsibility (CSR) events. This illustrates the significance attached to CSR events. In Ghana, a social disconnection may exist between the community and the construction sector. Therefore, this research aims to investigate the benefits of CSR in the construction industry, the implementation challenges and measures to enhance CSR in the Ghanaian built environment.Design/methodology/approach The qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
(127 reference statements)
4
5
0
Order By: Relevance
“…For others, refer to Table 3. Findings agree with Mersham andSkinner (2016), Duman et al (2016), Zhang et al (2019), Dawar and Singh (2021) and Aigbavboa et al (2024). Mersham and Skinner (2016) found a lack of information as a key factor hampered CSR.…”
Section: Csr In South Africasupporting
confidence: 87%
See 4 more Smart Citations
“…For others, refer to Table 3. Findings agree with Mersham andSkinner (2016), Duman et al (2016), Zhang et al (2019), Dawar and Singh (2021) and Aigbavboa et al (2024). Mersham and Skinner (2016) found a lack of information as a key factor hampered CSR.…”
Section: Csr In South Africasupporting
confidence: 87%
“…Findings agree with Buhmann (2006), Perry (2012), Samy et al (2015) and Aigbavboa et al (2024). Buhmann (2006) found that CSR affects more than just the business and the stakeholders.…”
Section: Ways To Enhance Csr In the Built Environmentsupporting
confidence: 78%
See 3 more Smart Citations